Unraveling the Veil of Speaking Anxiety: A Comprehensive Study of Indonesian EFL Learners at the Undergraduate Level - Nikita Putri Mahardika; Agus Widyantoro (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aimed to examine students’ anxiety in speaking: the students’ anxiety level, the differences between genders, and the factors contributing to it. It was a quantitative study that employed survey method. Descriptive analysis was used to evaluate the data, which were obtained using a closed-ended questionnaire disseminated using Google Forms. The finding revealed that most of the third-semester students of the English Department at a state university had speaking anxiety at a moderate level. Furthermore, it was reported that the anxiety that female and male students experienced did not significantly differ. However, male students were more anxious compared to female students. In addition, it was also found that the factor contributing the most was communication apprehension. In conclusion, the study has identified that students experienced anxious feelings in speaking class. Therefore, lecturers must be able to select teaching techniques that work effectively and create a safe space where students feel comfortable to speak.